Jaringan Pengelolaan Zakat untuk Pertumbuhan Industri Keuangan Non Bank Syariah - Ernawati Ernawati (Jurnal Ilmiah Ekonomi Islam, 2018)
Sharia non bank financial industry (IKNB) still low share of the conventional IKNB. The one of strategy to accelerating growth in sharia IKNB is through the management of zakah, infaq, sadaqah and awqaf (ZISWAF). This paper aims to explore the zakah management model for the growth of sharia IKNB. The secondary data were obtained through reports, information and zakat regulation. The analytical method used is descriptive and transaction cost approach. The results show that the growth of IKNBS can be accelerated with an active role of IKNBS in the ZISWAF management as a Unit Pengumpul Zakah (UPZ), besides partnership with Lembaga Amil Zakah (LAZ ). Partnership Model will minimize control and information cost of ZISWAF management. Lack of human resource and technological are the problems management zakah by sharia IKNB.